Development of a Problem Based Learning E-Module on Students Critical Thinking Abilities - Nurrahman, Candra Kusuma; Rusdarti, Rusdarti; Prihandono, Dorojatun (Journal of Economic Education, 2024)
Economic learning needs to be supported by learning media. In fact, at SMA Negeri 1 Kradenan, there is still little use of learning media. This learning media is really needed to realize students' critical thinking skills and learning motivation. It is necessary to develop an Economics E-Module as a learning medium. The research aims to determine the validity, effectiveness, critical thinking skills and learning motivation of students in learning using the Economics E-Module as a learning medium. The research method used is method Research and Development (R&D) 4-D. The research was carried out in class X of SMA Negeri 1 Kradenan, Kradenan District, Grobogan Regency. Non-test data was analyzed descriptively by percentage, while test data was analyzed using Mann-Whitney difference test analysis and analysis n-gain.The validation research results of expert lecturers obtained a very appropriate category, validation of economics teachers received a very appropriate category. Students' responses to the practicality of the Economics E-Module were categorized as very suitable for use, resulting in increased critical thinking skills and different learning motivation between the control class and the experimental class. The research concluded that the economics E-Module as a learning medium was declared very suitable by expert lecturers and economics teachers, effective for learning and able to improve students' critical thinking skills and learning motivation at SMA Negeri 1 Kradenan in the very good category.